Research status of intentional replantation fora single tooth with severe periodontal destruction - MENG Nan, WANG Bingna, MI Zhongqian, REN Xiuyun (Editorial Office of Stomatology, 2024)
With the development of regeneration technology, intentional replantation (IR) has gradually become the important treatment. Some affected teeth that are difficult to be cured by conventional methods, such as refractory periapical periodontitis, radicular groove and combined periodontal-endodontic lesions, can be preserved through IR. IR is effective in the treatment of teeth with severe periodontal destruction. This article reviews the historical development, clinical operation and influencing factors, and provides reference for exploring the treatment plan of IR for a single tooth with severe periodontal destruction and the preservation of patients' natural dentition.